Using informal learning experiences to enhance student learning outcomes in chemistry - Coll, S.; Treagust, David (2015)
© 2015 Sense Publishers. All Rights Reserved. Science and chemistry curricula worldwide encourage schools to draw upon nontraditional resources to enhance the learning of science and chemistry; in particular to engage in learning experiences outside the classroom or the school (LEOTC, LEOS). These experiences, it is argued, serve to increase motivation to learn science and allow teachers to better link real world experiences to classroom learning.